2020
DOI: 10.1016/j.scitotenv.2020.138699
|View full text |Cite
|
Sign up to set email alerts
|

Comment on: “A novel approach to peatlands as archives of total cumulative spatial pollution loads from atmospheric deposition of airborne elements complementary to EMEP data: Priority pollutants (Pb, Cd, Hg)” by Ewa Miszczak, Sebastian Stefaniak, Adam Michczyński, Eiliv Steinnes and Irena Twardowska

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Some elements, such as Pb and Hg, tend to bind strongly to organic material 50 . Lead is considered immobile and well-preserved in peat profiles 57 , 58 . Even most of the elements that represent the deposition of dust, such as Si and Zr, or others, such as Al, Ti, Sc and rare earth elements (REE), which are mainly identified as lithogenic tracers, should be immobile and stable 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Some elements, such as Pb and Hg, tend to bind strongly to organic material 50 . Lead is considered immobile and well-preserved in peat profiles 57 , 58 . Even most of the elements that represent the deposition of dust, such as Si and Zr, or others, such as Al, Ti, Sc and rare earth elements (REE), which are mainly identified as lithogenic tracers, should be immobile and stable 50 .…”
Section: Resultsmentioning
confidence: 99%
“…Two of these three studies are located in regions with no other data available (Serbia and north-western Canada; Refs. 8,11 ), and likely represent regional signals not yet reconstructed elsewhere, but calling for a denser network of sites in order to better constrain the inferred regional variability in Pb pollution. The anomalous record from Bolivia 31 , shows extreme variability and so is most likely a record of a very local pollution signal.…”
Section: Resultsmentioning
confidence: 99%
“…Building on the pioneering work of Clair Patterson, who established the context and significance of historical pollution [3][4][5] , numerous studies have reconstructed past Pb pollution based on geochemical and isotopic analysis of paleoenvironmental records 6 . Due to its chemical immobility and limited biological uptake, Pb is effectively locked in place after deposition onto various sedimentary environments 7,8 . Geochemical and isotopic analyses may thus provide reliable reconstructions of changing levels and provenance shifts of atmospheric Pb through time.…”
mentioning
confidence: 99%
“…The geochemical content of natural archives such as ice, marine sediment, and peat are often studied to investigate changing levels of anthropogenic pollution through time. Such studies exploit, among other tracers, the immobility of lead (Pb) in the environment, , interpreting changing Pb concentrations and/or isotopic ratios as indicators of changing levels and/or sources of air pollution. , An additional archive that is less frequently examined is stone weathering crusts. Pb concentrations in weathering crusts of historic urban built structures typically range from ten to hundreds of parts per million (ppm), reaching up to thousands of ppm when in the vicinity of industrial sites. This poses problems when Pb, together with other carcinogenic and toxic components, is remobilized and reintroduced into the overall urban pollution budget through processes such as cleaning (e.g., sandblasting), fire, weathering of surface coating such as lead-based paint, and common surface erosion. Indeed, recent studies on urban heavy metal dust have found an increasing risk to the environment and human health due to such remobilization of Pb. Therefore, there is an urgent need to advance our understanding of the interactions between the historic built environment and both ongoing and past environmental pollution accumulated in weathering crusts.…”
Section: Introductionmentioning
confidence: 99%
“…The geochemical content of natural archives such as ice, marine sediment, and peat are often studied to investigate changing levels of anthropogenic pollution through time. 1 3 Such studies exploit, among other tracers, the immobility of lead (Pb) in the environment, 4 , 5 interpreting changing Pb concentrations and/or isotopic ratios as indicators of changing levels and/or sources of air pollution. 6 , 7 An additional archive that is less frequently examined is stone weathering crusts.…”
Section: Introductionmentioning
confidence: 99%